Aging treatment method for nickel-based superalloy

Through the N-level aging treatment method of electrical pulses, combined with solid solution treatment and electrical pulse treatment, the problems of long aging treatment time and high energy consumption of nickel-based high-temperature alloys are solved, and more efficient heat treatment is achieved, improving the mechanical properties of the alloy and γ Distribution characteristics of 'phase.

CN119392133APending Publication Date: 2025-02-07LANZHOU JIAOTONG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411427758.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing nickel-based high-temperature alloys have a long aging treatment time and high energy consumption, making it difficult to meet the needs of efficient heat treatment.

Method used

The N-level aging treatment method of electrical pulses is adopted, and the combination of solid solution treatment and electrical pulse treatment is used to shorten the aging time and reduce energy consumption. The specific steps include water cooling after solid solution treatment, followed by N-level aging treatment of electrical pulses. The electrical pulse parameters include frequency 80-120Hz, duty cycle 5-20%, and peak current density gradually decreases.

Benefits of technology

The aging time of nickel-based high-temperature alloy is greatly shortened, energy consumption is reduced, the tensile strength and elongation of the alloy are improved, and the grain size of the γ′ phase is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392133A_ABST
    Figure CN119392133A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nickel-based superalloy heat treatment, and particularly relates to a nickel-based superalloy rapid aging heat treatment method. The method comprises the following steps: firstly, carrying out solution treatment on the nickel-based superalloy, and cooling an alloy sample subjected to the solution treatment in water to obtain a solution sample; and then the solid solution sample is subjected to electric pulse N-stage aging treatment. The Joule heating effect and the electromigration effect generated by the pulse current in the nickel-based superalloy are utilized to promote the transfer of solute atoms and the precipitation of gamma'phase, so that the aging time of the SLM-GH4099 nickel-based superalloy is greatly shortened, and the aging energy consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heat treatment of nickel-based high-temperature alloys, and in particular relates to a method for rapid aging treatment of nickel-based high-temperature alloys. Background Art

[0002] The GH4099 nickel-based superalloy prepared by selective laser melting (SLM) is a typical precipitation-strengthened superalloy, and the main precipitation-strengthening phase is the γ′ phase (γ′-Ni3(Al, Ti)). Due to the excellent comprehensive mechanical properties of the alloy, especially the high-temperature mechanical properties, it is widely used in high-temperature components such as turbine blades, combustion chambers, turbine disks, and jet ducts. These components need to have good high-temperature strength, oxidation resistance, and fatigue resistance. As a typical precipitation-strengthened superalloy, the precipitation of the γ′ phase during the aging process of the GH4099 nickel-based superalloy prepared by selective laser melting, including the size, morphology, and distribution of the γ′ phase, directly affects the service performance of the alloy.

[0003] At present, the selected SLM-GH4099 nickel-based superalloy is mainly heat treated by traditional aging process, with aging temperature of 700℃~900℃ and aging time of 5h~24h, so as to achieve full precipitation of γ′ phase. For example, in the paper "Study on Microstructure and Mechanical Properties of Selective Laser Melted GH4099 Superalloy", the SLM-GH4099 nickel-based superalloy reaches the highest tensile strength of 1240MPa at an aging temperature of 700℃ and a holding time of 16h, and the maximum elongation of 39.1% at an aging temperature of 800℃ and a holding time of 8h. For example, in the paper "Temperature-dependent Tensile Behavior of Additively Manufactured GH4099 Nickel-based Superalloy", the aging temperature of the SLM-GH4099 nickel-based superalloy is 800℃ and the aging time is 24h. The traditional aging process is time-consuming and resource-intensive. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides a method for rapid aging treatment of nickel-based high-temperature alloys, which can solve the problems of long aging time and high energy consumption in heat treatment of nickel-based high-temperature alloys.

[0005] To achieve the above object, the technical solution provided by the present invention is as follows:

[0006] In a first aspect, the present application provides a method for rapid aging treatment of a nickel-based high-temperature alloy, comprising the following steps:

[0007] S1: performing a solution treatment on a nickel-based high temperature alloy, and placing the alloy sample after the solution treatment into water for cooling to obtain a solution sample;

[0008] S2: subject the solution sample to N-level electric pulse aging treatment.

[0009] Among them, 3≤N≤7;

[0010] The peak current density of the first-level electric pulse is 48.39-51.61A / mm 2 ;

[0011] The peak current density of the electric pulse gradually decreases from level 1 to level N.

[0012] The peak current density of the last electric pulse is 32.26-35.48A / mm 2 .

[0013] Optionally, the first level electric pulse treatment time is 50 min-70 min, and the 2nd to Nth level electric pulse aging treatment time is 2-4 min for each level.

[0014] Optionally, the electric pulse parameters in the N-level electric pulse aging treatment are: frequency: 80-120 Hz, duty cycle: 5-20%, and a steady current mode is adopted during the same-level aging treatment.

[0015] Optionally, the nickel-based high-temperature alloy is an additively manufactured GH4099 nickel-based high-temperature alloy.

[0016] Optionally, the temperature of the solution treatment is 1100-1140° C., and the treatment time is 2-3 h.

[0017] Optionally, in S1, the alloy sample after the solution treatment is water-cooled to 10-40°C.

[0018] Optionally, after the electric pulse N-level aging treatment, the sample is cooled to room temperature in air.

[0019] Optionally, N is 5 levels, and the peak current density of the first level electric pulse is 51.61A / mm 2 , processing time 3610 s; the peak current density of the second-level electric pulse is 48.39A / mm 2 , treatment time 190 s, peak current density of the third level electric pulse is 45.16 A / mm 2 , treatment time 190 s, peak current density of the 4th level electric pulse is 41.94A / mm 2 , treatment time 190 s, peak current density of the 5th level electric pulse is 35.48A / mm 2 , processing time 190 s.

[0020] Optionally, the surface of the nickel-based high-temperature alloy is polished and then subjected to solid solution treatment.

[0021] Compared with the prior art, this application has at least the following beneficial effects:

[0022] The present invention promotes the transition of vacancies in nickel-based high-temperature alloys through electric pulse N-level aging treatment. The vacancy transition drives the transfer of more solute atoms, promotes the formation of GP zone, and provides a good foundation for the nucleation and precipitation of γ′ phase. The Joule heating effect and electromigration effect generated by pulse current in nickel-based high-temperature alloys are used to promote the transfer of solute atoms and the precipitation of γ′ phase, greatly shortening the aging time of SLM-GH4099 nickel-based high-temperature alloy and reducing aging energy consumption. The SLM-GH4099 nickel-based high-temperature alloy is subjected to electric pulse N-level aging treatment, and the aging time only needs 1-2h. The tensile strength of the nickel-based high-temperature alloy reaches 1231MPa, the elongation reaches 51.6%, and the average size of the γ′ phase grains is reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Flow chart of the electric pulse N-level aging treatment of the SLM-GH4099 nickel-based high-temperature alloy sample in Example 1;

[0024] Figure 2 This is a temperature variation diagram of the sample during the N-level aging treatment process using electric pulses in Example 1;

[0025] Figure 3 The figures are the crystal phase structure and particle size distribution of the samples obtained by different treatment methods in Examples 1-3; a and b are the corresponding results of the sample obtained in Example 1; c and d are the corresponding results of the sample obtained in Example 2; and e is the corresponding result of the sample obtained in Example 3.

[0026] Figure 4 The stress-strain curves of the samples obtained by different treatment methods in Examples 1-4;

[0027] Among them, 1. Nickel-based high-temperature alloy; 2. Box-type thermal resistance furnace; 3. Water bucket; 4. Aqueous solution; 5. Pulse power supply; 6. Infrared thermometer; 7. Wire. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0029] The experimental methods used in the embodiments of the present invention are conventional methods unless otherwise specified.

[0030] The reagents and materials used in this example can all be purchased conventionally. The quantitative experiments involved in the examples were repeated at least three times, and the results were averaged.

[0031] Source of raw materials:

[0032] The SLM-GH4099 nickel-based high-temperature alloy in the embodiment of the present application is a nickel-based high-temperature alloy SLM-GH4099 prepared by selective laser melting on a BLT-S615 system. The GH4099 powder particle size is 15 to 45 μm, the printing speed is 1000 mm / s, and the laser power is 250 W. The alloy composition of SLM-GH4099 is shown in the following table:

[0033]

[0034] Example 1

[0035] Processing flow chart Figure 1 As shown, the SLM-GH4099 nickel-based high-temperature alloy 1 is processed into a tensile specimen with a gauge section cross-sectional area of ​​3.1 mm×1 mm by using electric spark wire cutting, and the surface of the alloy tensile specimen is polished with sandpaper, and then the box-type resistance furnace 2 is heated to 1140°C, and the alloy tensile specimen processed by wire cutting is quickly placed in the box-type resistance furnace 2 for 2 hours. After the solution treatment is completed, the alloy specimen after the solution treatment is quickly placed in a bucket 3 containing an aqueous solution 4 and cooled to room temperature to obtain a solution specimen; the solution specimen is clamped on an electric pulse treatment fixture and connected to a pulse power supply 5 through a wire 7, and the specimen is subjected to an electric pulse N-level aging treatment, and the pulse current parameters are as follows: frequency is 100 Hz; duty cycle is 10%; a steady current mode is adopted under each aging, and the following N-level electric pulse treatments are performed in sequence: peak current density 51.61 A / mm 2 Processing time 3610s, peak current density 48.39A / mm 2 Treatment time 190s, peak current density 45.16A / mm 2 Processing 190s, peak current density 41.94A / mm 2 Treatment time 190s, peak current density 35.48A / mm 2 Treat for 190s. The sample temperature is tested by infrared thermometer 6: peak current density 51.61A / mm 2 The temperature is 840℃ and the peak current density is 48.39A / mm 2 The temperature is 805℃ and the peak current density is 45.16A / mm 2 The temperature is 770℃ and the peak current density is 41.94A / mm 2 The temperature is 730℃ and the peak current density is 35.48A / mm 2 The temperature is 650℃. After the treatment, the sample is air-cooled to room temperature 25℃. Then the oxide layer on the surface of the alloy sample is polished off with sandpaper to measure the sample size.

[0036] The mechanical properties of the sample treated with N-level electric pulse aging in Example 1 were tested, and the tensile strength was 1231 MPa and the elongation was 51.6%. The SEM photos and particle size distribution are shown in the figure. Figure 3 a and b. The time-temperature curve of the electric pulse N-level aging treatment is shown in Figure 2 shown.

[0037] Example 2

[0038] Use electric spark wire cutting to process the SLM-GH4099 nickel-based high-temperature alloy into a tensile specimen with a gauge section cross-sectional area of ​​3.1mm×1mm, use sandpaper to polish the surface of the nickel-based high-temperature alloy tensile specimen, then heat the box-type resistance furnace to 1140℃, and quickly put the wire-cut alloy tensile specimen into the box-type resistance furnace for 2h. After the solution treatment is completed, quickly put the solution-treated alloy specimen into a bucket filled with aqueous solution and cool it to room temperature. Then set the box-type resistance furnace to 800℃, quickly put the solution-cooled alloy tensile specimen to room temperature into the box-type resistance furnace for 24h, and finally quickly take out the alloy tensile specimen from the box-type resistance furnace and air-cool it to room temperature.

[0039] The mechanical properties of the heat-treated nickel-based high-temperature alloy in Example 2 were tested, and its tensile strength was 1237 MPa and its elongation was 42.38%. Figure 3 As shown in c and d.

[0040] Example 3

[0041] The SLM-GH4099 nickel-based high-temperature alloy was processed into a tensile specimen with a gauge section area of ​​3.1mm×1mm using electric spark wire cutting. The surface of the alloy tensile specimen was polished with sandpaper, and then the box-type resistance furnace was heated to 1140℃. The alloy tensile specimen processed by wire cutting was quickly placed in the box-type resistance furnace for 2 hours. After the solution treatment was completed, the alloy specimen after the solution treatment was quickly placed in a bucket containing an aqueous solution and cooled to room temperature to obtain a solution specimen; the solution specimen was clamped on the electric pulse treatment fixture and connected to the pulse power supply through a wire, and the specimen was subjected to electric pulse N-level aging treatment. The pulse current parameters were as follows: frequency was 100Hz; duty cycle was 10%; treatment was performed in steady current mode: peak current density was 16A for 3610s, and then the alloy tensile specimen was clamped on the electric pulse treatment fixture and connected to the pulse power supply through wire 7. The temperature measured by the infrared thermometer: peak current density 51.61A / mm 2 The temperature was 840℃. After the treatment, the sample was air-cooled to room temperature. Then the oxide layer on the surface of the alloy sample was polished off with sandpaper.

[0042] The mechanical properties of the alloy tensile specimen treated by direct cooling by electric pulse aging in Example 3 were tested, and its tensile strength was 899 MPa and its elongation was 58.9%. Figure 3 As shown in e.

[0043] Example 4

[0044] Processing flow chart as follows Figure 1 As shown, the SLM-GH4099 nickel-based high-temperature alloy 1 is processed into a tensile specimen with a gauge section area of ​​3.1mm×1mm by using electric spark wire cutting, and the surface of the alloy tensile specimen is polished with sandpaper, and then the box-type resistance furnace 2 is heated to 1140℃, and the alloy tensile specimen processed by wire cutting is quickly placed in the box-type resistance furnace 2 for 2h. After the solid solution treatment is completed, the alloy specimen after solid solution treatment is quickly placed in a bucket 3 containing an aqueous solution 4 and cooled to room temperature to obtain a solid solution specimen. The specimen is subjected to multi-stage aging treatment in an N-level resistance furnace, and the aging treatment is carried out in sequence: 840℃ for 3610s, 805℃ for 190s, 770℃ for 190s, 730℃ for 190s, and 650℃ for 190s. After the treatment, the specimen is air-cooled to room temperature. Subsequently, the oxide layer on the surface of the alloy specimen is polished off with sandpaper to measure the specimen size.

[0045] The mechanical properties of the sample subjected to multi-stage aging treatment in a box-type resistance furnace in Example 4 were tested, and the tensile strength was measured to be 1110.6 MPa and the elongation was 28.56%.

[0046] Depend on Figure 3 The three SEM images (a), (c), and (e) clearly show that the γ′ phase of the nickel-based high-temperature alloy treated by the electric pulse N-level aging treatment in Example 1 is large in number, small in size, and dispersed in distribution; while the γ′ phase of the alloy treated by the electric pulse aging direct cooling method in Example 3 is almost not precipitated. Figure 4 The stress-strain curves obtained by different treatment methods show that the comprehensive mechanical properties of the alloy treated by electric pulse N-level aging treatment are significantly better than those of the alloy treated by electric pulse direct cooling method or box-type resistance box multi-level aging treatment.

[0047] Depend on Figure 3 It can also be seen from the two grain size distribution histograms (b) and (d) that the average grain size of the alloy treated by aging in Example 2 is 48.35 nm, and the average grain size of the alloy treated by electric pulse N-level aging in Example 1 is 11.31 nm. It can be seen that the γ′ phase size of the alloy treated by electric pulse N-level aging treatment is significantly smaller than that of the conventional aging treatment.

Claims

1. A method for rapid aging treatment of nickel-based high-temperature alloys, characterized in that: The steps include: S1: performing a solution treatment on a nickel-based high temperature alloy, and placing the alloy sample after the solution treatment into water for cooling to obtain a solution sample; S2: subject the solution sample to N-level electric pulse aging treatment. Among them, 3≤N≤7; The peak current density of the first-level electric pulse is 48.39-51.61A / mm 2 ; The peak current density of the electric pulse gradually decreases from level 1 to level N. The peak current density of the last electric pulse is 32.26-35.48A / mm 2 .

2. The method for rapid aging treatment of nickel-based high-temperature alloy according to claim 1, characterized in that: The first level electric pulse treatment time is 50min-70min, and the second to Nth level electric pulse aging treatment time is 2-4 min each.

3. The method for rapid aging treatment of nickel-based high-temperature alloy according to claim 1, characterized in that: The electric pulse parameters in the electric pulse N-level aging treatment are: frequency: 80-120 Hz, duty cycle: 5-20%, and a steady current mode is adopted during the same aging treatment.

4. The method for rapid aging treatment of nickel-based high-temperature alloy according to claim 1, characterized in that: The nickel-based high-temperature alloy is an additively manufactured GH4099 nickel-based high-temperature alloy.

5. The method for rapid aging treatment of nickel-based high-temperature alloy according to claim 1, characterized in that: The temperature of the solution treatment is 1100-1140° C., and the treatment time is 2-3 h.

6. The method for rapid aging treatment of nickel-based high-temperature alloy according to claim 1, characterized in that: In S1, the alloy sample after the solution treatment is water-cooled to 10-40°C.

7. The method for rapid aging treatment of nickel-based high-temperature alloy according to claim 1, characterized in that: After the electric pulse N-level aging treatment, the sample was cooled to room temperature in air.

8. The method for rapid aging treatment of nickel-based high-temperature alloy according to claim 1, characterized in that: The N is 5 levels, and the peak current density of the first level electric pulse is 51.61A / mm 2 , processing time 3610 s; the peak current density of the second-level electric pulse is 48.39A / mm 2 , treatment time 190 s, peak current density of the third level electric pulse is 45.16 A / mm 2 , treatment time 190 s, peak current density of the 4th level electric pulse is 41.94A / mm 2 , treatment time 190 s, peak current density of the 5th level electric pulse is 35.48A / mm 2 , processing time 190 s.

9. The method for rapid aging treatment of nickel-based high-temperature alloy according to claim 1, characterized in that: The surface of the nickel-based high-temperature alloy is polished and then subjected to solid solution treatment.

Citation Information

Cited By

  • Manufacturing method of stress lasting type Inconel 718 high-temperature alloy precision rod bolt

    CN120244486A